2002
DOI: 10.1046/j.1365-2419.2002.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrographic phenomena influencing early life stages of the Sicilian Channel anchovy

Abstract: The information collected from a European Union funded project on the ‘Distribution Biology and Biomass Estimates of the Sicilian Channel Anchovy (Engraulis encrasicolus)’ was used to analyse the linkage between the general circulation pattern of the Atlantic Ionian Stream (AIS) and the reproductive strategy of the Sicilian Channel anchovy. The main spawning ground is located in the NW region of the southern Sicilian coast. This region is a stable area of low current produced by the impingement towards the coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(52 citation statements)
references
References 18 publications
3
30
0
Order By: Relevance
“…This latter situation probably coincides with unfavourable conditions in terms of prey availability in the Sicilian Channel. Although primary productivity at lower trophic levels may be increased by deep/ cool water upwelling enhancing the circulation of nutrients, negative SST anomalies may have a negative physiological influence, delaying fish development (Lafuente et al 2002). Studies on fish population in this area have shown that sardine and anchovy biomass are negatively correlated with the mean SST in periods corresponding to larval and juvenile growth, resulting in a reduction in recruitment success and thereby also population size (e.g.…”
Section: Pre-breeding Period Environmental Conditions Influence Skippmentioning
confidence: 99%
See 2 more Smart Citations
“…This latter situation probably coincides with unfavourable conditions in terms of prey availability in the Sicilian Channel. Although primary productivity at lower trophic levels may be increased by deep/ cool water upwelling enhancing the circulation of nutrients, negative SST anomalies may have a negative physiological influence, delaying fish development (Lafuente et al 2002). Studies on fish population in this area have shown that sardine and anchovy biomass are negatively correlated with the mean SST in periods corresponding to larval and juvenile growth, resulting in a reduction in recruitment success and thereby also population size (e.g.…”
Section: Pre-breeding Period Environmental Conditions Influence Skippmentioning
confidence: 99%
“…Studies on fish population in this area have shown that sardine and anchovy biomass are negatively correlated with the mean SST in periods corresponding to larval and juvenile growth, resulting in a reduction in recruitment success and thereby also population size (e.g. Lafuente et al 2002). In particular, Marettimo storm petrel colonies are located at the western inlet of the Sicilian Channel, where the 2 large Mediterranean sub-basins meet, resulting in the bifurcations of the surface and intermediate-depth water transports (Pierini & Rubino 2001).…”
Section: Pre-breeding Period Environmental Conditions Influence Skippmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we consider the Strait of Sicily, which is known to govern the exchanges between the eastern and western basins and is characterized by active mesoscale dynamics (Lermusiaux and Robinson, 2001), strongly influencing the ecology of phytoplankton communities. Moreover, the Strait of Sicily is a biologically rich area of the Mediterranean Sea with a key role in terms of fisheries (Lafuente et al, 2002;Cuttitta et al, 2003). The anchovy growth (along with phytoplankton biomass) in the Sicilian Channel resulted to be mainly explained by changes in the chlorophyll concentration, used as a phytoplankton biomass indicator (Basilone et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the efforts of several international programs focused on the study of the biology of fish larvae (Miya, 1995;Noell, 2003), their assemblages (McGowen, 1993;Sanvicente-An˜orve et al, 1998) and relationship with the environment (Olivar, 1990;Lafuente et al, 2002), our current knowledge on the relationship between total abundance of fish larvae and zooplankton biomass (hereinafter termed Fl & Zoo) is still limited. Some authors have attempted to describe such a relationship (Ali Khan & Hempel, 1974;Loeb, 1979;Ciechomski & Sa´nchez, 1983;Cowan & Shaw, 1991;Rodrı´guez & Rubı´n, 1991), and some have restricted their interpretation to only one species of fish (Townsend, 1983;Cowan & Shaw, 1991).…”
Section: Introductionmentioning
confidence: 99%